Latest Project Management Trends and Challenges with COVID-19 - Savio, Raj (Eximia, 2021)
Since the COVID-19 crisis struck, organizations in vulnerable sectors worldwide have seen their revenues drop substantially in a matter of weeks — in some cases, dwindling to almost nothing. Countless companies have taken reactive and efficient steps to ward off major losses, such as establishing remote work arrangements, securing supply chains, reducing employee workload, cutting costs, and applying for government support. However, as the COVID-19 continues its disruption, the livelihood of many entrepreneurs and small business owners continues to remain threatened.